Analysis of Financial Statements Based on Financial Ratio and Vertical-Horizontal Method in PT Unilever, Tbk, 2016-2017 Period - Nova Tri Anggraini (Journal of Social Science, 2022)
This research aims to horizontally and vertically determine the financial performance of PT Unilever, Tbk, especially by observing the development of assets and financial statements through the calculation of financial ratios. Based on the research results, it can be observed that based on the analysis of the ratio of Liquidity, Profitability and Leverage tend to fluctuate. The liquidity ratio has increased, Profitability ratio has increased in GPM and NPM but decreased in Cash Ratio, ROA, and ROE. The Leverage Ratio has decreased; thus, the financial performance of PT Unilever, Tbk has not been fully optimal. Based on the horizontal analysis, it can be concluded that the balance sheet and income statement of PT Unilever, Tbk are optimal. Based on the vertical analysis, it can be concluded that the balance sheet and income statement index of PT Unilever, Tbk are optimal